Physical-therapeutic alternative for dysatrics in patients with West Syndrome. (RIAF. International Journal of Physical Activity, 2025)
A consent for different authors exists that they consider that the dysarthria constitutes an enough frequent diagnosis within the patients with neurological alterations of Syndrome of West, which considers a factor that can affect his quality of life itself. Objetive: For what this study presented itself like objective elaborating a physical therapeutic alternative that contribute to the improvement of the dysarthria in patients with Syndrome of West. Materials y Methods: A designing of descriptive research, with a mixed focus as from the utilization combined of empiric methods is assumed for it and mathematical statisticians to obtain information, his processing and assessment. Results: The found results denote the need of bigger telling functionality, maximizing the efficacy and spontaneity of communication. Conclusions: So that the proposal focuses on the aspects socioemotional and improvement of autonomy and these patients' functionality, he must contribute it in the improvement of the functioning of the upset of the language and this population's quality of life, contributing to optimize the sanitary attention.
Keywords: West's Syndrome; Epilepsy; Epileptic Pediatric Syndrome; Intervention Neuropsychological